Perceptions of Chinese students in an Australian university: Are we meeting their needs? - Briguglio, Carmela; Smith, R. (Routledge, 2012)
This short-term longitudinal study sought to identify the issues faced by a group of international Chinese students undertaking study in an Australian university. While the focus was on educational issues, socio-cultural and personal factors were also examined in an attempt to identify the sorts of strategies students used in settling into anew socio-cultural and educational context. Interviews conducted at the beginning and end of the first semester of study indicate a range of issues that are supported by previous studies. What has not previously been highlighted, however, is the emphasis on speaking and listening skills which students reported they needed to improve. Lack of proficiency in these areas was seen by students as hampering their active participation in class, leading to lack of confidence in approaching Australian students, and resulting in their inability to benefit from the “Australian experience”. Many existing academic support structures in Australian universities tend to emphasize support with written and study skills. While this is important because of the direct impact on assessment, it is perhaps now opportune to place some emphasis on developing strategies and programmes that will support the development of students’ speaking and listening skills, with a focus on intercultural communication.